Analysis and Design of Wage Structure and Scale Based on The Two-Point Method (Case Study of Small Businesses in the Culinary Sector Assisted by Jakpreneur in 2023 in South Jakarta) - Togi, Ehug; Kartika, Lindawati (Jurnal Ilmiah Sumber Daya Manusia, 2024)
Business in the culinary sector is considered profitable because food is one of the basic needs that is unavoidable for humans. This study examines the development of recommendations for the structure and wage scale for SME practitioners. The objectives of this study are: (1) To identify the financial compensation received by employees of Small Businesses in the culinary sector. (2) To analyze the internal and external compensation comparisons for small businesses. (3) To formulate an ideal and effective wage structure and scale for employees in the culinary sector. The data type used in this study is quantitative data, and the data sources are obtained from primary data (direct interviews, questionnaires) and secondary data obtained from the South Jakarta city government website, the Central Statistics Agency, and other and articles and other scientific literature. The methods used are descriptive methods including mode, salary survey, salary mapping, and the two-point method. The research findings reveal 8 critical positions, with 4 critical positions (general manager, supervisor, driver, social media admin) still having compensation levels below the external survey. Furthermore, this research provides recommendations for wage structure and scale that can serve as references for msmes development.